Hydrogen isotope effect on thermodynamic properties of Pd0.9X0.1 (X = Cu, Ag and Au) alloys. (2nd February 2017) - Anand, N.S.; Pati, Subhasis; Jat, Ram Avtar; Parida, S.C.; Mukerjee, S.K.
Abstract: The effect of hydrogen isotopes on the thermodynamic parameters of desorption reaction in the Pd0.9 X0.1 -H2 /D2 systems (X = Cu, Ag and Au) were investigated using Sieverts' apparatus. The hydrogen/deuterium desorption pressure-composition-temperature profiles generated in this study revealed substantial hydrogen isotope effect on the equilibrium plateau pressures with P eq (D2 ) >  P eq (H2 ). A correlation was observed for the trend in equilibrium plateau pressures with the unit cell sizes of the Pd0.9 X0.1 alloys. Hydrogen isotope separation factor was determined for all these alloys and Pd0.9 Cu0.1 alloy was found to have highest separation factor. The results of equilibrium plateau pressure and the separation factor for Pd0.9 Cu0.1 alloys merits its candidature for its applicability in gas chromatographic separation of hydrogen isotopes. Highlights: PCT profiles for Pd0.9 X0.1 -H2 /D2 systems (X = Cu, Ag and Au) were generated. Trend in lattice constant was correlated with plateau pressures of these systems. Thermodynamic parameters for these systems were derived. Hydrogen isotope separation factor was derived. Pd0.9 Cu0.1 alloy has favorable properties for gas chromatographic separation.